DIFFERENCES BETWEEN FOOTBALL PLAYERS OF DIFFERENT GAMING POSITIONS BASED ON SOME BASIC AND SPECIFIC MOTOR ABILITIES - Bogdan Tomić; Slavko Molnar; Miroslav Radoman (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Based on the structure competition activities, and its character can be defined as a hypothetical model of the anthropological characteristics of football players of different gaming positions. Based on hypothetical models of different football players' position can make a division into two groups of players based on game systems that are commonly used in modern football, which is 4-4-2, and the common anthropological characteristics, structure and nature of activities carried out by during the game, so the first group consists of players with smaller volumes of engagement in the game (goalkeeper, two central defenders and two strikers) and the second group 190 CRNOGORSKA SPORTSKA AKADEMIJA, "Sport Mont" časopis br. 31,32,33. consists of players with greater scope to engage in the game (two foreign players and four defensive midfielder (midfielder) ). The aim is to determine the difference between players of different players' positions on the basis of some basic and specific motor abilities. The sample of 206 football players aged 18 ± 0.5 years is divided into 5 subsamples according to examinees gaming position: forwarders (45), midfield players (47), defenders (41), central defenders (44) and goalkeepers (29). The battery of 16 tests (in which the results are expressed in distance and time - metric). It can be concluded that there are differences between players of different players' positions on the team in relation to the basic and specific motor skills.